How green primary iron production in South Africa could help global decarbonization. (7th February 2022) - Trollip, Hilton; McCall, Bryce; Bataille, Chris
ABSTRACT: The production of iron and steel is one of the largest global sources of industrial greenhouse gas (GHG) emissions. South Africa (SA) could competitively export near-zero embodied GHG primary iron to steelmakers in leading decarbonizing markets. A green primary iron production process substitutes hydrogen for coke as the iron ore reductant. A SA plant would enjoy most of its competitive cost advantage from hydrogen produced using very low-cost solar photovoltaic electricity. In import markets, using the European Union (EU) as an example, steelmakers could use imported green primary iron to increase utilization of electric arc furnaces while reducing total EU demand for clean electricity (i.e. for hydrogen for reduction needs) and thereby lower total system costs of decarbonization. SA could bolster crucial export and tax revenues while moving towards a broader transition to a sustainable industry. Three things are needed to unlock new global business models involving the relocating of green primary iron production to regions with abundant renewable energy: (1) a steelmaker with access to a hydrogen reduction technology appropriate for SA's ores willing and able to invest in a plant; (2) access to a bankable lead market for that plant's production; and (3) international trade rules and emissions accounting related to the carbon content of commodities that enable the reconfiguration of supply chains to reduce global decarbonization costs. Key policy insights: Green primary iron production in SA could increase value added from local iron ore and solar energy resources, bolster exports and initiate transformation to a sustainable industry. Green primary iron imports from SA to the EU could reduce the cost of overall decarbonization while increasing the competitiveness of steel product manufacturing. Enabling conditions include a willing steelmaker, fair access to the EU iron market, enabling trade rules, and embodied emissions certification and accounting. Green primary iron imports can reduce demands on EU low carbon electricity supply, lowering electricity prices and increasing energy security. The collaboration envisioned between the EU and SA could help develop the framework for future inter-regional decarbonization strategies for other commodities and other countries.